Prior Anticoagulation in Patients with Ischemic Stroke and Atrial Fibrillation. Issue 1 (17th October 2020) - Meinel, Thomas R.; Branca, Mattia; De Marchis, Gian Marco; Nedeltchev, Krassen; Kahles, Timo; Bonati, Leo; Arnold, Marcel; Heldner, Mirjam R.; Jung, Simon; Carrera, Emmanuel; Dirren, Elisabeth; Michel, Patrik; et al.
Abstract : Objective: The aim was to evaluate, in patients with atrial fibrillation (AF) and acute ischemic stroke, the association of prior anticoagulation with vitamin K antagonists (VKAs) or direct oral anticoagulants (DOACs) with stroke severity, utilization of intravenous thrombolysis (IVT), safety of IVT, and 3‐month outcomes. Methods: This was a cohort study of consecutive patients (2014–2019) on anticoagulation versus those without (controls) with regard to stroke severity, rates of IVT/mechanical thrombectomy, symptomatic intracranial hemorrhage (sICH), and favorable outcome (modified Rankin Scale score 0–2) at 3 months. Results: Of 8, 179 patients (mean [SD] age, 79.8 [9.6] years; 49% women), 1, 486 (18%) were on VKA treatment, 1, 634 (20%) on DOAC treatment at stroke onset, and 5, 059 controls. Stroke severity was lower in patients on DOACs (median National Institutes of Health Stroke Scale 4, [interquartile range 2–11]) compared with VKA (6, [2–14]) and controls (7, [3–15], p < 0.001; quantile regression: β −2.1, 95% confidence interval [CI] −2.6 to −1.7). The IVT rate in potentially eligible patients was significantly lower in patients on VKA (156 of 247 [63%]; adjusted odds ratio [aOR] 0.67; 95% CI 0.50–0.90) and particularly in patients on DOACs (69 of 464 [15%]; aOR 0.06; 95% CI 0.05–0.08) compared with controls (1, 544 of 2, 504 [74%]). sICH after IVT occurred in 3.6% (2.6–4.7%) of controls, 9 of 195 (4.6%; 1.9–9.2%; aOR 0.93; 95% CI 0.46–1.90) patients on VKA and 2 of 65 (3.1%; 0.4–10.8%, aOR 0.56; 95% CI 0.28–1.12) of those on DOACs. After adjustments for prognostic confounders, DOAC pretreatment was associated with a favorable 3‐month outcome (aOR 1.24; 1.01–1.51). Interpretation: Prior DOAC therapy in patients with AF was associated with decreased admission stroke severity at onset and a remarkably low rate of IVT. Overall, patients on DOAC might have better functional outcome at 3 months. Further research is needed to overcome potential restrictions for IVT in patients taking DOACs. ANN NEUROL 2021;89:42–53